Nutrition and feeding of organic poultry [ - Blair, Robert , 1933- (CABI, 2008)
Deals with feeding organic poultry and presents advice on selecting suitable ingredients, preparing appropriate feed mixtures and integrating them into organic poultry production systems. This book outlines the international standards of organic feeding and the species and breeds of poultry most suitable for organic farming.